Choice of allocation norms and perceived fairness of Malaysian corporate management - Khaliq, Ahmad (Emerald, 2004)
This empirical study based on a survey in Malaysian organizations was conducted to investigate perceived justice in distribution of organizational resources. It was designed to study the issues such as recruitment, promotion, performance appraisal and distribution of other perks and benefits to the workforce. Assuming value differences in the major ethnic groups in the country, namely Malays, Chinese, Indians, and others, the study however, expected differences in allocation decisions made only in Malay and Chinese majority organizations.